Habilidades comunicativas de adultos mayores pertenecientes a una fundación de la ciudad de Cartagena (2019)
Objective: The communication skills of the elderly population of Granitos de Paz Foundation of Cartagena city were characterized. Methodoly: The cross-sectional descriptive observational research design was applied; the sample consisted of 180 older citizens belonging to the Granitos de Paz Foundation of the city of Cartagena. The instrument was applied, Battery for the evaluation of aphasic disorders (BEAD), and later the results were tabulated with Microsoft Excel and the analysis was made with the statistical program SPSS.22.0 (Statistical Package for the Social Sciences), using descriptive statistics. Results: It was evidenced that in the population of 60 older adults between the ages of 60 to 89 years evaluated of the Granitos de Paz Foundation of the city of Cartagena, the predominant gender was the female with 85% and the male with 15%, belonging in its entirety to stratum 1 and it was found that 65% of those evaluated reached primary education, 21.7% secondary education and 13.3% never attended school. Through the application of the instrument, Battery for the evaluation of aphasic disorders (BEAD), it was found that 98.3% of the older adults evaluated had a good performance and 1.7% a regular performance in the variable oral comprehension. Regarding oral production, the majority of the population with 53.3% presented a good performance, 45% a regular performance and 1.7% a bad performance. With regard to reading, 91.7% of the older adults evaluated had a good result, a regular 6.7% and a poor 1.7%, and in terms of writing, 76.7% of the population of older adults had a good result, 18.3% regular and 5% bad. Conclusion: It was established that despite age, the elderly belonging to the Granitos de Paz Foundation of the city of Cartagena, for the most part, adequately developed the processes evaluated by the Battery for the evaluation of aphasic disorders (BEAD), highlighting that in most of these processes there was no evidence of bad results..